MODEL AKUNTABILITAS KINERJA SKPD DALAM MEWUJUDKAN GOOD GOVERNANCE - M. Zawawi (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Accountability is the obligation of government institutions to account, to answer and explain the success or failure in performing basic tasks and functions to his superiors and the public in the form Accountability Report. The instrument used is called accountability systems that accommodate the Government Performance Strategic Management consists of the Strategic Plan, Performance Plan, Measurement and Assessment and Reporting Performance. This research studied about how the preparation of SAKIP, Government Performance and Accountability factors influencing AKIP as well as AKIP and models that agree with the meaning accountability. Aim to describe and analyze the preparation SAKIP. Yet the unsuccessful implementation of SAKIP because of: a) low competence in preparing SAKIP, b) The limited guidance and direction from the competent authorities c) the limited time allowed. d) The absence of strong sanctions. This research is practically recommended in order to: a) Formulate SAKIP accordance with the guidelines and norms, b) Provide opportunities for the communities involved and the target involved in the process of implementing an SAKIP. c) Undertake an internal Evaluation and dissemination of SAKIP products to the public so they can enjoy the results and benefits. d) To enhance the competence of personnel in charge of implementing SAKIP through education and training, e) Provide guidance and direction in the form of intensive mentoring.Keyword : System Accountability, Government Performance, Strategic Management.